ANALISIS MAKNA SIMBOLIK DALAM PAKAIAN ADAT DAN ASESORIS SUKU ABUIDI DESA LEMBUR BARAT KABUPATEN ALOR - Vera M. Kabey; Vani E. Maninyeni; Yolanda Laumai; Yosin Djolelang, Yesgelode Lauata, Welmince Onbila, Halena Muna Bekata, Petrus Mau Tellu Dony (Adisam Publisher, 2025)
The purpose of this study is to examine the symbolic meaning in the traditional clothing and accessories of the Abui tribe in Lembur Barat Village, Alor Regency. The research method used is a qualitative approach with observation techniques, in-depth interviews, and literature studies. The results show that the motifs in the woven fabrics of the Abui tribe reflect the relationship of the community with nature, ancestors, and highly-regarded traditional values. Certain colours in traditional clothing have symbolic meanings related to courage, purity, and wisdom. In addition, accessories such as headbands, beaded necklaces, and metal bracelets have a function not only as decoration, but also as spiritual protection and group identity. Based on the results of the research, it can be concluded that this research confirms that the traditional clothing and accessories of the Abui Tribe are not merely cultural products, but also a means of symbolic communication that reflects their belief system and social structure. By understanding this symbolic meaning, it is hoped that the cultural heritage of the Abui Tribe can continue to be preserved and appreciated as part of the cultural wealth of Indonesia.